What’s new in the treatment of female pelvic inflammatory disease? - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Pelvic inflammatory disease (PID) is a large group of inflammatory polymicrobial illnesses of female genital organs, mostly caused by Chlamydia trachomatis and Neisseria gonorrhoeae. When poorly treated it leads to some serious distant side effects e.g. impaired fertility. Quinolones play an important role in the treatment of PID, whereas newly introduced moxifloxacin is characterized by high therapeutic efficacy and safety.